2013
DOI: 10.1016/j.pnpbp.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Neural predictors and mechanisms of cognitive behavioral therapy on threat processing in social anxiety disorder

Abstract: Cognitive behavioral therapy (CBT) is “gold standard” psychotherapy for social anxiety disorder (SAD). Cognitive models posit that preferential processing of threat mediates excessive forms of anxiety, which is supported by exaggerated amygdala, insula, and cortical reactivity to threatening socio-emotional signals in SAD. However, little is known about neural predictors of CBT success or the mechanisms by which CBT exerts its therapeutic effects. Functional magnetic resonance imaging (fMRI) was conducted duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
114
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 77 publications
17
114
0
2
Order By: Relevance
“…Precentral and postcentral gyri are involved in somatosensory processing and voluntary movement and have also been shown to activate during emotion regulation (Buhle et al, 2014;Goldin et al, 2008;Kohn et al, 2014). Though these regions have previously been related to treatment response in anxious adults (Klumpp et al, 2013;Phan et al, 2013), very …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Precentral and postcentral gyri are involved in somatosensory processing and voluntary movement and have also been shown to activate during emotion regulation (Buhle et al, 2014;Goldin et al, 2008;Kohn et al, 2014). Though these regions have previously been related to treatment response in anxious adults (Klumpp et al, 2013;Phan et al, 2013), very …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, activation in the amydala, involved in signaling the presence of threat, has been shown to predict response to treatment in anxiety (McClure et al, 2007a;Whalen et al, 2008); however, results have been inconsistent. Less amygdala reactivity in adults with GAD predicted better response to venlafaxine (Whalen et al, 2008), yet greater amygdala activation predicted better response to CBT or fluoxetine in anxious youth (McClure et al, 2007a), and other studies have failed to find amygdala effects (Doehrmann et al, 2013;Klumpp et al, 2013;Nitschke et al, 2009). Other work has indicated that greater activation to threatening faces in visual processing regions (ie, occipital and temporal gyri) involved in detecting and appraising emotional cues predicted better response to CBT among adults with social anxiety disorder (Doehrmann et al, 2013;Klumpp et al, 2013), possibly indicating greater initial threat reactivity which can be modified by treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Klumpp and colleagues showed emotional faces to SAD individuals before and after treatment and found decreased responsivity in the insula, the dmPFC and the mOFC after CBT (Klumpp, Fitzgerald, & Phan, 2013a). Combined Internet-delivered CBT and escitalopram treatment for SAD dampened amygdala responsivity to emotional faces (Gingnell et al, 2016), furthering the support for the notion that the amygdala may be a common anxiolytic pathway for various SAD treatments (Furmark et al, 2002).…”
Section: Cognitive Behaviour Therapymentioning
confidence: 94%